Neue Inschriften von Olympia - Taeuber, Hans (2013)
The ancient sanctuary of Olympia, the birthplace of the Olympic Games and of athletic competion in general, has been fascinating people from antiquity up to the present time. In the present volume, all inscriptions - large and small - published after Dittenberger's edition are collected, critically edited, translated into German, and commented. Complete Greek and Latin indices make the inscriptions easily accessible to all scholars interested in the ancient Olympic Games, in the history of religion and sports, and in classical studies in general.